2010
DOI: 10.1094/cchem-87-3-0231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Outer Bran Layers from Germinated Wheat Grains on Breadmaking Properties

Abstract: Wheat grains were germinated in the dark at room temperature (24°C) for 1, 2, 3, 5, and 8 days. Germinated wheat grains were pearled in a Waring blender, and the outer bran layers were separated from the pearled grains. Breadmaking was performed with wheat flour and 10% of the outer bran layer. Breadmaking properties (bread height [mm] and specific volume [cm3/g]) were gradually enhanced by blending the germinated outer bran layers, and maximum specific volume was obtained after 5 days of germination. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…Sound cereal grains have low endogenous peptidase activity levels, which increase substantially after 1 day of sprouting (Elmoneim, Elkhalifa, & Bernhardt, ; Faltermaier, Zarnkow, Becker, Gastl, & Arendt, ; Kolodziejczyk & Michniewicz, ). A 2‐ to 5‐fold increase in peptidase activity has been observed in sorghum (Elmoneim et al., ), barley (Osman et al., ), rye (Kolodziejczyk & Michniewicz, ), oats (Mäkinen, Zannini, & Arendt, ), and wheat (Faltermaier et al., ; Seguchi, Uozu, Oneda, Murayama, & Okusu, ) when sprouted for 3 to 7 days at 15 to 27 °C. Endopeptidases are produced and secreted from the aleurone layer and scutellum during sprouting.…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 95%
See 1 more Smart Citation
“…Sound cereal grains have low endogenous peptidase activity levels, which increase substantially after 1 day of sprouting (Elmoneim, Elkhalifa, & Bernhardt, ; Faltermaier, Zarnkow, Becker, Gastl, & Arendt, ; Kolodziejczyk & Michniewicz, ). A 2‐ to 5‐fold increase in peptidase activity has been observed in sorghum (Elmoneim et al., ), barley (Osman et al., ), rye (Kolodziejczyk & Michniewicz, ), oats (Mäkinen, Zannini, & Arendt, ), and wheat (Faltermaier et al., ; Seguchi, Uozu, Oneda, Murayama, & Okusu, ) when sprouted for 3 to 7 days at 15 to 27 °C. Endopeptidases are produced and secreted from the aleurone layer and scutellum during sprouting.…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 95%
“…Chung et al., ; Kaur, Singh, & Singh, ; Ogbonna, Abuajah, Ide, & Udofia, ; Swieca & Dziki, ; Van Hung, Maeda, Yamamoto, & Morita, ; Vis & Lorenz, ; J. Xu et al., ). However, some studies have reported a significant decrease of 3% to 10% of the protein content in sprouted wheat (Seguchi et al., ), sorghum (Afify, El‐Beltagi, El‐Salam, & Omran, ; Elmaki et al., ), or rice (Esa, Kadir, Amom, & Azlan, ; Mohan, Malleshi, & Koseki, ; Veluppillai, Nithyanantharajah, Vasantharuba, Sandrasegarampillai, & Arasaratnam, ). In contrast, other studies have reported an increase in protein content of 5% to 10% in sprouted barley (Donkor et al., ; Teixeira, Nyman, Andersson, & Alminger, ), oats (Donkor et al., ), wheat (Donkor et al., ), sorghum (Donkor et al., ), rye (Donkor et al., ), rice (Donkor et al., ; Ohtsubo, Suzuki, Yasui, & Kasumi, ; Pal et al., ; Watanabe, Maeda, Tsukahara, Kayahara, & Morita, ), and millet (Mbithi‐Mwikya et al., ).…”
Section: Biochemical and Physicochemical Changes In Cereal Grains As mentioning
confidence: 99%
“…Various approaches, including manipulation of bran particle sizes (Cai, Choi, Hyun, Jeong, & Baik, 2014;DeKock et al, 1999), bran fermentation and enzymatic treatment (Katina et al, 2012;Salmenkallio-Marttila, Katina, & Autio, 2001), germination (Seguchi, Uozu, Oneda, Murayama, & Okusu, 2010), incorporation of enzymes into WWF formulations (Katina, Salmenkallio-Marttila, Partanen, Forssell, & Autio, 2006), bran hydration and physical treatments such as autoclaving and freezing (Cai, Choi, Park, & Baik, 2015), have been introduced to modify bran and improve dough properties as well as the bread-baking quality of WWF products. Cai et al (2015) reported that WWFs supplemented with bran preautoclaved at 121°for 2 hr and hydrated to 60% moisture produced bread with significantly higher loaf volume.…”
Section: Introductionmentioning
confidence: 99%
“…Improved resistance to extension was probably linked to the solubilization of AX. Activation of endogenous xylanase and amylase by germination has been observed to improve the properties of bran-enriched doughs (Seguchi et al 2010). Altered rheology with overall improvement in gas production and retention was correlated with improved bread volume in PLS analysis, and it may explain the improved technological functionality of the fermented and enzyme-treated brans.…”
Section: Discussionmentioning
confidence: 92%